Midwives' approach to the prevention and repair of obstetric perineal trauma in Spain - Estíbaliz Laderas Díaz; Julián Rodríguez‐Almagro; Rafael Picón Rodríguez; Juan Miguel Martínez Galiano; Sandra Martínez Rodríguez; Antonio Hernández‐Martínez (Wiley, 2024)
Abstract Aim Different clinical practice guidelines include recommendations on how to prevent and repair obstetric perineal trauma, as well as the use of episiotomy. To evaluate the variability in midwives' professional practices for preventing and repairing perineal trauma, as well as the professional factors that may be associated with the restrictive use of episiotomy. Design Observational cross‐sectional study. Methods Three hundred five midwives completed an anonymous questionnaire developed by the authors and distributed across various midwifery scientific societies. The main outcomes measured were the frequencies of adopting specific practices related to perineal injury prevention and repair, episiotomy technique and restrictive episiotomy use (<10%). Odds ratios (OR) and adjusted odds ratios (aOR) with 95% confidence intervals were estimated. Results Intrapartum perineal massage was not normally used by 253 (83%) of midwives, and 186 (61%) applied compresses soaked in warm water to the perineum. Regarding episiotomy, there was a great deal of variability, noting that 129 (42.3%) adopted a restrictive use of this procedure, 125 (41%) performed it between 10% and 20%, while 51 midwives (16.7%) performed it in more than 20% of cases. In addition, 165 (54.1%) midwives followed an incision angle of 60º. Concerning tears, 155 (50.8%) usually sutured first‐degree tears and 273 (89.5%) always sutured second‐degree tears. Midwives attending home births (aOR = 6.5; 95% CI: 2.69-15.69), working at a teaching hospital (aOR = 3.69; 95% CI: 1.39-9.84), and the ones who recently completed their professional training (aOR = 3.58; 95% CI: 1.46-8.79) were significantly more likely to adopt a restrictive use of episiotomy. Conclusions There is a significant variability in Spanish midwives' practices for preventing and repairing perineal tears. Moreover, the restrictive use of episiotomy is associated with midwives attending home births, working in teaching hospitals and having recent professional training. Patient or Public Contribution No patient or public contribution.